Partitioning of energy and degradability of browse plants in vitro and the implications of blocking the effects of tannin by the addition of polyethylene glycol - Baba, A.S.H.; Castro, F.; Ørskov, E.R. (Elsevier Masson, 2002)
The gas production in vitro method was used to evaluate the degradability and gas production of browse plants in the absence or presence of polyethylene glycol 8000 (PEG). Substrates (leguminous and browse plants; 500 mg) were incubated for 24 h and the accumulated gas produced recorded. The incubation contents of the syringes were transferred into nylon bags and the undegraded residues weighed after washing and drying to constant weight (syringe-nylon bag (SNB) method). Substrates were also incubated in the rumen in nylon bags for 24 h to determine in sacco degradability. Gas production ranged between 10.3 and 64.4 ml whereas dry matter degradation ranges between 27.3 and 70.9%. Addition of PEG, which minimised the inhibitory effects of tannin on microbial fermentation resulted in an increase in both gas production and degradability in vitro, which ranged from 25.7 to 64.2 ml and 34.2 to 75.0%, respectively. Correlation analysis of the DM degradability estimated by the SNB method and in sacco method was greater in the presence of PEG (y = 0.71x + 14.9; r2 = 0.92) compared with absence of PEG (y = 0.59x + 15.0; r2 = 0.72). Partitioning factor (PF) of substrate to gas, which was expressed as mg DM degraded/ml gas, reflects the variation in microbial biomass yield. The PF figures, which varied from 4.94-11.05 to PF+PEG values of 4.74-6.84 upon the addition of PEG, indicate the inhibitory effects of tannins on gas production. This suggests the presence of tannin has a potentially beneficial effect to protein nutrition of the host animal by altering partitioning of nutrients towards higher microbial yield rather than short chain fatty acids. PF values of browse plants determined both in the absence and presence of PEG may indicate the relative importance of tannins in different plant species on substrate degradability and partitioning of nutrients. © 2002 Elsevier Science B.V. All rights reserved.